Correlations among nicotine dependence, health-related quality of life, and depression in current smokers: a cross-sectional study with a mediation model - Xiong, Huali; Ma, Fengxun; Tang, Dayi; Liu, Daiqiang (Frontiers in Psychiatry, 2024)
A cross-sectional study named "Psychology and Behavior Investigation of Chinese Residents" was conducted from July 10 to September 15, 2021 in China. Nicotine dependence, HRQoL and depression were measured by Fagerstrom Test for Nicotine Dependence (FTND) , the European Five Dimensional Five Level Health scale(EQ-5D-5L) and the 9-item Patient Health Questionnaire (PHQ-9) respectively. Information on age, gender, place of residence, household registration, education level, marital status, employment status, average family monthly income, drinking frequency, living status, BMI, multiple chronic conditions were also collected. Pearson's correlation test and logistic regression analysis were conducted to explore the association between nicotine dependence, HRQoL and depression and a mediation analysis was applied to explore the mediating effect of the HRQoL on this relationship. Results A total of 1,381 current smokers were included in the study. The participants showed a moderate level of nicotine dependence with a mean of 1.36(SD=1.50) , a relatively high level of HRQoL scores (Mean=0.94, SD=0.13), and a depression score with a mean of 6.48(SD=6.09). Approximately 22.74% (314/1,381) of the participants were considered to indicate depression. In the univariable regression model, it was found that nicotine dependence was positively associated with depression (OR:1.094, 95%CI: 1.008-1.187), while HRQoLwas negatively associated with depression (OR:0.011, 95%CI: 0.004-0.033). In the multivariable regression model, HRQoL was still notably associated with depression (OR:0.008, 95%CI: 0.002-0.027), however, the positive association was not observed between nicotine dependence and depression. The Pearson's correlation test demonstrated that nicotine dependence was negatively correlated with HRQoL(rs= -0.147, P＜0.001) and HRQoL was negatively correlated with depression(rs= -0.275, P＜0.001) . In contrast, nicotine dependence was positively correlated with depression(rs= 0.136, P＜0.001). Mediation analysis found that HRQoL moderated the relationship between nicotine dependence and depression with a mediating effect of 26.49%. Conclusions The findings support that nicotine dependence is positively associated with depression and HRQoL is negatively associated with depression in current smokers. HRQoL mediated the relationship between nicotine dependence and depression. The well-established imperative interventions aimed at promoting smoking cessation and improving quality of life may benefit for alleviation of depression in current smokers.